2019
DOI: 10.1021/acs.est.8b06963
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation of Polystyrene by Dark (Tenebrio obscurus) and Yellow (Tenebrio molitor) Mealworms (Coleoptera: Tenebrionidae)

Abstract: Yellow mealworms (larvae of Tenebrio molitor, Coleoptera: Tenebrionidae) have been proven to be capable of biodegrading polystyrene (PS) products. Using four geographic sources, we found that dark mealworms (larvae of Tenebrio obscurus) ate PS as well. We subsequently tested T. obscurus from Shandong, China for PS degradation capability. Our results demonstrated the ability for PS degradation within the gut of T. obscurus at greater rates than T. molitor. With expanded PS foam as the sole diet, the specific PS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
169
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 259 publications
(206 citation statements)
references
References 47 publications
(119 reference statements)
13
169
0
5
Order By: Relevance
“…With the same protocols, the PS-degrading capability was also documented in a broader range of mealworms from 12 different locations worldwide, indicating that PS degradation in mealworms is ubiquitous . This discovery also inspired researchers to explore more insect species, such as dark mealworms (Tenebrio obscurus) (Peng et al, 2019) and superworms (Zophobas atratus) (Yang et al, 2020), that also could eat and degrade PS.…”
Section: Pementioning
confidence: 99%
“…With the same protocols, the PS-degrading capability was also documented in a broader range of mealworms from 12 different locations worldwide, indicating that PS degradation in mealworms is ubiquitous . This discovery also inspired researchers to explore more insect species, such as dark mealworms (Tenebrio obscurus) (Peng et al, 2019) and superworms (Zophobas atratus) (Yang et al, 2020), that also could eat and degrade PS.…”
Section: Pementioning
confidence: 99%
“…However, although the foam feeds can maintain the insect's life and produce eggs, it was not economically feasible (Nukmal et al, 2018). Tenebrio obscurus has also been proposed as a likely candidate to be able to degrade plastics (Peng et al, 2019).…”
Section: Environmentmentioning
confidence: 99%
“…Recently, several plastic-ingesting worms capable of removing plastic wastes have been reported, including waxworms ( Galleria mellonella L.), mealworms ( Tenebrio molitor L.) and superworms ( Zophobas atratus L.), which can depolymerize polyethylene (PE) and polystyrene (PS) upon ingestion [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. Further studies have shown that treatment with antibiotic compounds to remove gut bacteria within the worms significantly reduces the biodegradation efficiency with respect to ingested PE and PS, suggesting that gut bacteria participate in plastic biodegradation in these worms [ 9 , 10 , 15 ]. Several gut bacterial species isolated from worms have been verified to be able to mediate plastic biodegradation directly.…”
Section: Introductionmentioning
confidence: 99%